Worker wellbeing and productivity in advanced economies: Re-examining the link - Amy Isham (Ecological Economics, 2021)
Labour productivity is a key concept for understanding the way modern economies use resources and features prominently in ecological economics. Ecological economists have questioned the desirability of labour productivity growth on both environmental and social grounds. In this paper we aim to contribute to ongoing debates by focusing on the link between labour productivity and worker wellbeing. First, we review the evidence for the happy-productive worker thesis, which suggests labour productivity could be improved by increasing worker wellbeing. Second, we review the evidence on ways that productivity growth may undermine worker wellbeing. We find there is experimental evidence demonstrating a causal effect of worker wellbeing on productivity, but that the relationship can also sometimes involve resource-intensive mediators. Taken together with the evidence of a negative impact on worker wellbeing from productivity growth, we conclude that a relentless pursuit of productivity growth is potentially counterproductive, not only in terms of worker wellbeing, but even in terms of long-term productivity.